A retrospective analysis of clinical characteristics of childhood narcolepsy. Issue 6 (5th March 2018) - Dhanju, Simranpal; Al-Saleh, Suhail; Amin, Reshma; Weiss, Shelly K; Zweerink, Allison; Toulany, Alene; Murray, Brian J; Narang, Indra
Abstract: Aim: Narcolepsy, encompassing excessive daytime sleepiness (EDS), cataplexy, sleep paralysis and hypnogogic hallucinations, was previously considered rare in childhood. Recently, cases of childhood narcolepsy have increased significantly and the reasons for this may include the increasing awareness of narcolepsy as well as the H1N1 vaccination. The aim of this study was to describe the clinical characteristics of childhood narcolepsy, specifically focusing on cataplexy subtypes that may facilitate early recognition of narcolepsy. Methods: We retrospectively reviewed and analyzed the medical records of 33 children diagnosed with narcolepsy at the Hospital for Sick Children, in Toronto, Ontario. All patients were seen prior to 18 years of age and symptoms were self-reported by parents and/or children themselves. Results: At presentation, 32 of 33 children reported EDS and 28 of 33 reported cataplexy. Among the 28 patients with cataplexy, 18 of 28 reported cataplexy referred to as 'cataplectic facies' (e.g., facial hypotonia and/or tongue protrusion) while 10 of 28 patients reported characteristic cataplexy, defined as bilateral loss of muscle tone. Children with cataplectic facies reported higher BMI z-scores compared to those with characteristic cataplexy, 1.8 and 0.8, respectively. Children with cataplectic facies also tended to be younger than those with characteristic cataplexy, 9.2 and 11.8 years of age, respectively. Cataplectic facies appear to be related to narcolepsy close to disease onset. Conclusions: Children, especially young, obese children, presenting with a history of EDS with associated facial hypotonia or tongue protrusion raises the index of suspicion of narcolepsy and should prompt a referral to a specialized sleep facility to establish the diagnosis.